Analisis Rasio Likuiditas Dan Solvabilitas Terhadap Kinerja Keuangan Perusahaan Pada PT Nippon Indosari Corpindo Tbk - Anisa Pujianti; Ageng Setiani Rafika; Eduard Hotman Purba (UNIVERSITAS RAHARJA, 2023)
A company's financial health may be evaluated via financial analysis using liquidity ratios and solvency ratios. These analyses provide light on a company's asset management prowess and the importance of lowering operational and financial risks, but in different ways. Analysis of liquidity ratios and solvency in the context of PT. Nippon Indosari Corpindo Tbk might shed further light on the state of the company's operations. Financial reports filed with the Indonesia Stock Exchange are used for study of liquidity ratios and solvency ratios by PT. Nippon Indosari Corpindo Tbk. This study falls under the category of descriptive quantitative research since it utilizes numerical data from an annual financial report to conduct an in-depth analysis and interpretation of the fiscal performance of PT. Nippon Indosari Corpindo Tbk for the 2020–2022 time frame. Strategies for gathering information from existing written sources. The analytical method employs the use of ratios such as the Current Ratio, the Quick Ratio, the Debt to Assets Ratio, and the Debt to Equity Ratio. PT Nippon Indosari Corpindo Tbk's annual financial statements, namely the statement of financial status, serve as the basis for this research. The Indonesia Stock Exchange serves as the source for the company's yearly financial statements (IDX). Study findings on the company's financial health Solvability Ratio and the other liquidity ratios are used by PT. Nippon Indosari Corpindo (Debt to Assets Ratio, Debt to Equity Ratio).